A New Homoisoflavonoid from Flue-Cured Tobacco and Its Anti-tobacco Mosaic Virus Activity - Li, Yinke; Wang, Fei; Yuan, Ting; Yang, Guangyu; Hu, Qiufen; Wang, Zhengyin (Asian Journal of Chemistry, 2015)
A new homoisoflavonoid, tabeanin A (1), was isolated from the stems of flue-cured tobacco (a variety of Nicotiana tabacum L). Its structure was elucidated by spectroscopic methods, including extensive 1D and 2D NMR techniques. Compound 1 was also tested for its anti-tobacco mosaic virus activity and it shows potential anti-tobacco mosaic virus activity with inhibition rates of 36.8 %.